La experiencia emocional del profesional de enfermería en UCI durante la pandemia de la COVID-19 (2022)
A pandemic emergency is a great benchmark for a health crisis and represents a challenge for humanity. For the health area, the COVID-19 crisis, the current pandemic event, has meant a hospital overload and therefore to the health system (1). The health personnel who must face the pandemic, are seen exposed to combat and deal with the consequences of the SARS-Cov-2 virus in the general population, which in turn brings with it alterations in the state physical, psychological, emotional, labor and social, intervening in turn in the field nursing staff professional in health (1). Nursing work is intended to provide, preserve the care and well-being of patients, is essential when facing the health crisis. The Nursing has gained a greater weight in society in recent times and more during the health crisis, due to the high demand for professionals and their commitment to the preservation of life. Without fear of providing care, the professional nurse and nursing technician has positioned himself as the personal with more presence in health care during the COVID 19 pandemic (1). Considering the high demand for the Intensive Care Unit service (ICU). Due to the increase in patients with SARS-Cov-2, a increase in nursing professionals, due to the current crisis (2). There are various areas where nursing has required greater support during the pandemic due to the emotional load that one comes to have in the field of work, consequences that were not contemplated, they arrived with the COVID-19 pandemic, highlighting especially the Intensive Care Unit (ICU), due to the high requirement of professional health attitudes, all this motivated by the clinical complexity of patients with COVID-19, to whom the professional nurse had to generate an adaptation to the way you use your work, implementing restrictive forms of greater care and protection with any type of contact, trying to prevent the spread of the virus and thus have greater biosecurity (2). 6 Nursing professionals who provide their services in the ICU experience events that transform their work and social environment, where they are also highlighted the emotional experiences that accompany the events experienced (2), Generating changes in your routine, implementing new biosecurity measures, for which you want to get to know the emotional experiences obtained according to the changes required by the intensive care unit.